2016
DOI: 10.5468/ogs.2016.59.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic hysterectomy via suture and ligation technique

Abstract: ObjectiveThe term 'total laparoscopic hysterectomy (TLH) with classical suture method' refers to a surgical procedure performed using only sutures and ligations with intracorporeal or extracorporeal ties, without using any laser or electronic cauterization devices during laparoscopic surgery as in total abdominal hysterectomy. However, the method is not as widely used as electric coagulation equipment for TLH because further advances in technology and surgical technique are required and operative time can take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…used RUMI ® System in their study and they found the mean hospitalization duration of 4.1 days. [ 31 ] On the other hand, Mitri et al . found the mean length of hospital stay 1 day.…”
Section: Discussionmentioning
confidence: 99%
“…used RUMI ® System in their study and they found the mean hospitalization duration of 4.1 days. [ 31 ] On the other hand, Mitri et al . found the mean length of hospital stay 1 day.…”
Section: Discussionmentioning
confidence: 99%
“… 45 On the other hand, suturing of excessive tissue during vaginal cuff ligation can induce too much tension and cause ureteral obstruction by kinking. 46 Thus, urinary tract injury is one of the inherent risks associated with TLH.…”
Section: Resultsmentioning
confidence: 99%
“…In FINHYST study in Finland, the rates of ureteral or bladder injury in TLH/LH performed in 2006 was indicated as 0.3% or 1.0% . An institute of Korea reported that the rates of ureteral or bladder injury as the postoperative complications in TLH from 2005 to 2014 were totally 0.4% or 0.8%, however, after 2010, no complication occurred by the improvement of surgical technique . A single institute in Japan reported that the rates of ureteral and bladder injury was 0.32%, and 0.48%, respectively, in total 1253 TLH by using early ureteral identification technique .…”
Section: Discussionmentioning
confidence: 99%